Molecular surveillance of tick‐borne diseases affecting horses in Poland—Own observations. Issue 4 (23rd February 2021) - Teodorowski, Oliwier; Kalinowski, Marcin; Winiarczyk, Dagmara; Janecki, Radosław; Winiarczyk, Stanisław; Adaszek, Łukasz
Abstract: The purpose of the study was to carry out the molecular surveillance of piroplasmosis, granulocytic anaplasmosis and lyme borreliosis in horses which originated from Poland and exhibited symptoms raising the suspicion of the aforementioned disease units. The presence of Theileria equi genetic material was detected in 37 out of 512 examined horses (7.2%), and Anaplasma phagocytophilum in 9 (1.8%). The DNA of Borrelia burgdorferi was found in 11 out of 204 examined horses (5.4%). The above‐cited results indicate that the problem of tick‐borne diseases affecting horses in Poland is not as significant as in other parts of Europe, however they have to be considered in differential diagnosis of the diseases with lethargy, fever, anaemia and thrombocytopenia. Abstract : Tick‐borne diseases such as piroplasmosis, granulocytic anaplasmosis and lyme borreliosis are a recently new problem among horses in Poland. In Poland, piroplasmosis is amongst the most frequent of the tick‐borne diseases diagnosed in horses, whereas granulocytic anaplasmosis is the least frequent. The results of the molecular surveillance of tick‐borne diseases indicate that they do not pose such a significant problem among horses in Poland in comparison to the other parts of Europe. However, they have to be considered in differential diagnosis of the diseases with lethargy, fever, anaemia and thrombocytopenia.